Activation of Src, Fyn and Yes non-receptor tyrosine kinases in keratinocytes expressing human papillomavirus (HPV) type 16 E7 oncoprotein - Szalmás, Anita (BioMed Central, 2013)
BACKGROUND: The Src family tyrosine kinases (SFK) are cellular regulatory proteins that influence cell adhesion, proliferation, invasion and survival during tumor development. Elevated activity of Src was associated with increased cell proliferation and invasivity in human papillomavirus (HPV)-associated malignancies; therefore, transduced human foreskin keratinocytes (HFK) were used to investigate whether SFK activation is a downstream effect of papillomaviral oncoproteins. Activation of ubiquitously expressed SFKs, namely Src, Yes and Fyn, was investigated in both proliferating and differentiating keratinocytes. RESULTS: In proliferating keratinocytes, Src, Yes and Fyn mRNA levels were not affected by HPV 16 E6 or E7 oncoproteins, while at the protein level as detected by western blot, the presence of both E6 and E7 resulted in substantial increase in Src and Yes expression, but did not alter the high constitutive level of Fyn. Phospo-kinase array revealed that all ubiquitously expressed SFKs are activated by phosphorylation in the presence of HPV 16 E7 oncoprotein. Keratinocyte differentiation led to increased Yes mRNA and protein levels in all transduced cell lines, while it did not influence the Src transcription but resulted in elevated Src protein level in HPV16 E7 expressing lines. CONCLUSIONS: This study revealed that HPV 16 oncoproteins upregulate Src family kinases Src and Yes via posttranscriptional mechanisms. A further effect of HPV 16 E7 oncoprotein is to enhance the activating phosphorylation of SFKs expressed in keratinocytes.